New species of Stenopterobia (Bacillariophyta) from Colombia and Peru, and new nomenclatural transfers in Iconella - Sala, Silvia E.; Guerrero, José M.; Avellaneda, Marcela Núñez; Kociolek, John P. (Phytotaxa, 2021)
During a survey of diatoms from the Colombian and Peruvian Amazon, we encountered many specimens of the genus Stenopterobia in periphyton and plankton samples. These diatoms were assigned to three different taxa, two with sigmoid valves and the other one with straight valves. The comparison of their valve morphologies with similar taxa described in the literature revealed that they do not correspond to any previously known taxa. They are described herein as Stenopoterobia caquetaensis sp. nov., S. colombiana sp. nov. and S. amazonica sp. nov. We maintain this genus assignment since the new taxa, as well as other species currently in Stenopterobia, exhibit differences from Iconella, a genus to which several Stenopterobia species were recently transferred. Differences exist between the two genera in their ultrastructural features, such as plain internal valve face and unrimmed internal areolar openings, which do not fully conform to the description of Iconella. Additionally, the robustoid Surirella rafaelii and S. tayronarum, recently described from Colombia, are transferred to Iconella.